Faktor- Faktor Yang Berhubungan Dengan Ruptur Perineum Pada Ibu Bersalin Di Tpmb Bidan Elis Susilawati: to determine the factors associated with perineal rupture in mothers giving birth at TPMB Midwife Elis Susilawati, Amd. Keb in 2022. - Wapa Latipatunnisa; Indah Sri Wahyuni; Nurul Syuhfal (Politeknik Karya Husada, 2024)
Background: Perineal rupture is a condition that occurs quite often during normal childbirth. In Indonesia, perineal rupture is experienced by 75% of mothers giving birth vaginally. Of the total of 1,951 spontaneous vaginal births, 57% of mothers received perineal sutures, 28% due to episiotomy and 29% due to spontaneous tears. Objective: to determine the factors associated with perineal rupture in mothers giving birth at TPMB Midwife Elis Susilawati, Amd. Keb in 2022. Method: the type of research used is a descriptive and analytical survey using a cross-sectional research design, data was taken from patient medical resumes with a sample of 195 people from a population of 382 mothers giving birth. Results: Based on age p=0.004, the OR value shows that respondents whose age is at risk have a 2.6 times chance. Based on parity p=<0.001 the OR value shows that respondents with parity are at risk 4.4 times. Based on the birth weight of the baby p=0.022 The OR value shows that respondents with an abnormal birth weight have a 2.7 times chance. Based on birth distance, p=<0.001, the OR value shows that respondents with a birth distance at risk have a 9.2 chance of experiencing perineal rupture. Conclusion: It was found that there was a relationship between perineal rupture and age, parity, birth weight and birth spacing. To reduce the high rate of perineal rupture, midwives are expected to take part in supportive training, so that they can minimize the incidence of perineal rupture, and provide counseling to pregnant women to prepare for childbirth. Keywords: Baby's birth weight, birth interval, parity, age, perineal rupture